2018
DOI: 10.1002/ejic.201800182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fe(OH)3 Microtubes at the Gas–Solution Interface and Their Use for the Fabrication of Fe2O3 and Fe Microtubes

Abstract: A straightforward and effective method is reported for obtaining microtubes of iron-based compounds by interfacial interaction between a solution and gaseous reagents. A thin amorphous film of Fe(OH) 3 was synthesized on the surface of a mixed FeCl 2 /FeCl 3 /ascorbic acid aqueous solution as a result of the interaction with gaseous ammonium. When dried in air, the film was oxidized and transformed into microtubes. These Fe(OH) 3 microtubes were converted into α-Fe 2 O 3 ones by annealing in air. As a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…As was shown in ref. , microtubes with roll morphology are formed after drying a thin gradient film in the air at room temperature. Thus, the main force inducing the rolling process of the film is due to different surface states, namely, to the composition and density gradient of the two film sides.…”
Section: Resultsmentioning
confidence: 99%
“…As was shown in ref. , microtubes with roll morphology are formed after drying a thin gradient film in the air at room temperature. Thus, the main force inducing the rolling process of the film is due to different surface states, namely, to the composition and density gradient of the two film sides.…”
Section: Resultsmentioning
confidence: 99%
“…Fe(OH) 3 gradually decomposes with the increase in temperature; when the temperature reaches 500 °C, the Fe(OH) 3 completely decomposes into α-Fe 2 O 3 with a total weight loss of about 10.2 %. [38][39][40] In the S@FH composites sample, the material weight loss comprises the evaporation of sulfur and the decomposition of Fe(OH) 3 . Considering the weight loss of S@FH composites (61.9 %) and the established ratio (60 : 40) between sulfur and Fe(OH) 3 within the composites, it can be inferred that the final sulfur content of the S@FH composites is 57.82 %, (61.9 %À (10.2 %×40 %) = 57.82 %).…”
Section: Resultsmentioning
confidence: 99%
“…The curve for sulfur shows that the weight loss temperature ranges from 242 °C to 381 °C. Fe(OH) 3 gradually decomposes with the increase in temperature; when the temperature reaches 500 °C, the Fe(OH) 3 completely decomposes into α‐Fe 2 O 3 with a total weight loss of about 10.2 % [38–40] . In the S@FH composites sample, the material weight loss comprises the evaporation of sulfur and the decomposition of Fe(OH) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The nanoparticles' crystallite size was calculated using Debye Scherrer's formula [21]. Figure 9 shows the pattern of [ZnO: Fe2O3/ Eug]; there was more crystallinity of ZnO-Fe2O3 and different intensities of diffraction peaks [18], which matched with 01-080-0075 [22] and 01-084-0311 [23]. From Table 4, it can be concluded that the diffraction angles return to Fe2O3 and ZnO as individual elements.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 94%